OPTIMIZATION OF PHYSICO-CHEMICAL PARAMETERS FOR HYPER-PRODUCTION OF LYSINE BY MUTATED STRAIN OF BREVIBACTERIUM FLAVUM - S. Irshad; A. S. Hashmi; M. M. Javed; M. E. Babar; A. R. Awan; A. A. Anjum (Journal of Animal and Plant Sciences, 2015)
Lysine as an essential amino acid supplemented to fulfil the dietary requirement of Poultry feed. In Pakistan all this demand is accomplished by importing lysine for feed sector. Wild Brevibacterium flavum was used to induce mutation by random mutagenesis for hyper production of lysine through fermentation. The highest lysine producing strain (BFENU2) was screened with 21.64 g/L production by mutation treatment of (ENU).It was used for physico- chemical optimization of cultural medium. Molasses with 15 brix having 10- 12% sugar was found optimum for lysine production (25.88g/L) with optimized fermentation period of 48 hours. During optimization of physical parameters significantly (P< 0.05) high yield of lysine 26.69 g/L was produced by 4% inoculum at 30oC and pH 7 with pre- optimized substrate. The optimum concentration of 0.3% NH4(SO4)2 and 0.2% urea was found significant (P< 0.05) with high concentration of Lysine (29.34 g/L) production. The optimum level of CaCO3 2% was found statistically (P< 0.05) significant that produced 29.84 g/L of Lysine. The inclusion of optimum soybean hydrolysate (0.5%) and tryptone (0.3%) significantly enhance the titre of Lysine (33.92 g/L). Thus after optimization of various physical and chemical parameters Lysine production enhanced much than wild strain hence these optimum levels can be used for mass production of lysine on pilot scale.
Keywords: Mutated strain; Brevibacterium flavum; optimization; physico- chemical; hyper- production